FRI0001 IL-17 producing-DN T cells are expanded in the blood, infiltrate salivary glands and are resistant to corticosteroids in sjÖgren's syndrome. (23rd January 2014) - Alunno, A.; Bistoni, O.; Bartoloni, E.; Caterbi, S.; Bigerna, B.; Tabarrini, A.; Mannucci, R.; Beghelli, D.; Falini, B.; Gerli, R.
Abstract : Background: The discovery of IL-17-producing CD4 + T helper (Th17) cells challenged the long-standing paradigm of Th1/Th2 cell immune response and shed some light on the pathogenic mechanisms of systemic autoimmune disorders. IL-17 in a pro-inflammatory cytokine which mediates target organs damage during the disease. To note, it has been recently observed that asmall CD3 + T-cell population, that lacks of both CD4 and CD8 molecules, defined as double negative (DN), is expanded in the peripheral blood of patients with systemic lupus erythematosus, produces IL-17 and accumulates in the kidney during lupus nephritis. Objectives: Since IL-17 production is enhanced in salivary gland infiltrates of patients with primary Sjögren's syndrome (SS), we aimed to investigate whether DN T cells may be involved in the pathogenesis of salivary gland damage Methods: Thirty patients with SS and 16 normal controls (NC) were enrolled. CFSE-stained PBMCs were cultured in anti-CD3-coated plates in presence or absence of dexamethasone (Dex) at different concentrations. Phenotypic characterization was performed by flow cytometry in freshly isolated cells and after culture using anti-CD3, CD4, αβ-TCR, γδ-TCR, RORγt, IL-17 antibodies and respective isotypes. SS minor salivary glands (MSG) were processed for immunofluorescence staining. Results: Total circulating DN T cells were increased in SS compared to NC. This was due to an increase of both αβ-TCR + and γδ-TCR + cells. NC and SS freshly isolated DN T cells express RORγt and produce consistent amounts of IL-17. Notably, DN T cells were found in the SS-MSG infiltrate. αβ-TCR +, but not γδ-TCR +, DN T-cell expansion in SS was dependent on disease activity according to the EULAR Sjögren's syndrome disease activity index (ESSDAI). Dex was able to down-regulate IL-17 in vitro production in NC and SS CD4 + cells and in NC DN T cells, but not in DN T cells from SS samples. Conclusions: DN T cells are expanded in SS PB, produce IL-17 and infiltrate SS MSG. The expansion is dependent on disease activity. In SS, conventional Th17 cells are inhibited by Dex, but DN T cells appear to be resistant to this effect. The recognition of a pathogenic T-cell subset, that appears to be in vivo activated and not sensitive to CS, in an autoimmune disorder such as SS may represent an intriguing finding with potential therapeutic implications of great interest. References: Crispin C et al. J Immunol 2008;181:8761 Nguyen CQ et al. Arthritis Rheum 2008;58:734 Disclosure of Interest: None Declared